2014
DOI: 10.1007/s10652-014-9368-x
|View full text |Cite
|
Sign up to set email alerts
|

Wind effect on diurnal thermally driven flow in vegetated nearshore of a lake

Abstract: In this study, a highly idealized model is developed to discuss the interplay of diurnal heating/cooling induced buoyancy and wind stress on thermally driven flow over a vegetated slope. Since the model is linear, the horizontal velocity can be broken into buoyancy-driven and surface wind-driven parts. Due to the presence of rooted vegetation, the circulation strength even under the surface wind condition is still significantly reduced, and the transient (adjustment) stage for the initial conditions is shorter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Further efforts have been paid to incorporate the vertical variation of horizontal velocities in the depth-integrated models [35,36], but the vertical stratification has yet to be addressed. Lin and Wu [37,38] and Lin [39] examined thermally-driven flows over vegetated sloping bottoms with an idealized, linear, vertically-solved slice analytical model. It was reported that vegetation can significantly change the circulation pattern of the open water zone to a large extent.…”
Section: Introductionmentioning
confidence: 99%
“…Further efforts have been paid to incorporate the vertical variation of horizontal velocities in the depth-integrated models [35,36], but the vertical stratification has yet to be addressed. Lin and Wu [37,38] and Lin [39] examined thermally-driven flows over vegetated sloping bottoms with an idealized, linear, vertically-solved slice analytical model. It was reported that vegetation can significantly change the circulation pattern of the open water zone to a large extent.…”
Section: Introductionmentioning
confidence: 99%
“…The phasing of the flow response relative to the diurnal surface heat flux forcing will depend on the dynamic regimes for the buoyancy and cross-shore momentum balances (Farrow and Patterson 1993;Monismith et al 2006). Although the various mechanisms described above can provide intermittent perturbations to the thermally driven crossshore exchange, persistent forcing mechanisms, such as diurnal winds (Farrow 2013;Lin 2015) and tidally driven alongshore currents, can lead to systematic variability in the regular cross-shore exchange pattern.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the non-linear effects, especially heat advection produced by a sharp change of vegetation distribution, are ignored. The effect of weak wind on thermal-induced circulation as [27] and [28] mentioned needs to be addressed in stratified environments. Also, the rooted emergent vegetation is assumed to have no effect on light extinction coefficients in the water body.…”
Section: Resultsmentioning
confidence: 99%